Formulation and Evaluation of the Physical Stability of Liquid Soap Preparations with Sonneratia caseolaris Leaf Extract - Muhammad Syarif Hidayatullah; Andi Zsazsa Rafiatul Muklis; Raisha Hamiddani Syaiful; Nur Mahdi (Journal of Pharmacology Experiment and Pharmaceutical Technology, 2025)
Red pidada leaf (Sonneratia caseolaris L.) is a plant that has benefits as an antioxidant with active compounds such as alkaloids, flavonoids, tannins, terpenoids, and saponins. Usually the local community uses this plant as a wet pupur. The purpose of this study was to determine whether red pidada leaves can be formulated into a liquid soap preparation that meets the requirements of physical properties and stability evaluation. This type of research is true experimental laboratory. Extraction of red pidada leaves is carried out by maceration using ethanol as a solvent. The formulation used three extract concentrations, namely F1 (2%), F2 (4%), and F3 (8%). Parameters carried out in the form of physical properties testing, including organoleptic test, pH, specific gravity, viscosity, foam resistance and stability testing with the cycling test method. The results of organoleptic physical properties testing on the three formulations showed that the F1 preparation was light brown, F2 brown, and F3 dark brown, had a distinctive aroma and had a liquid consistency in F1 and slightly thick in F2 and F3. Testing of pH, specific gravity, viscosity and foam resistance in the three formulations has met the requirements, except for the specific gravity test in the F3 preparation. Testing with the cycling test method has affected the evaluation of physical properties in the three formulations which causes a very thick consistency in the preparation. So that the tests that meet the requirements are only the pH and foam resistance tests, while the specific gravity is only in the F1 preparation.